Komponen-Komponen dan Model Pengembangan Kurikulum PAI di Sekolah (IJM: Journal of Multidisiplinary, 2024)
Islamic Religious Education (PAI) in schools requires a comprehensive and effective curriculum development. This research aims to understand the components and models of PAI curriculum development in several secondary schools in the Surakarta region. A qualitative approach with an analytical descriptive method was employed in this study to explore in-depth and detailed aspects of Islamic Religious Education (PAI) curriculum development. Data were collected through various techniques, including in-depth interviews, participatory observation, and documentation studies, providing a comprehensive and accurate overview of the topic. The results of this study revealed that the main components of PAI curriculum development encompass several important aspects. Some of the curriculum development models used are the Tyler model, Hilda Taba model, administrative model, Oliva model, and Beauchamp model. By paying attention to and developing each of these components and models, the PAI curriculum can enhance the understanding and application of Islamic values in students' daily lives.